Charge transport properties of SARS-CoV-2 Delta variant (B.1.617.2). (October 2022) - He, Lijun; Xie, Zhiyang; Long, Xing; Zhang, Chaopeng; He, Chengyun; Zhao, Boyang; Qi, Fei; Zhang, Nan
Abstract: The B.1.617.2 (Delta) variant of concern is causing a new wave of infections in many countries. In order to better understand the changes of the SARS-CoV-2 mutation at the genetic level, we selected six mutations in the S region of the Delta variant compared with the native SARS-CoV-2 and get the conductance information of these six short RNA oligonucleotides groups by construct RNA: DNA hybrids. The electronic characteristics are investigated by the combination of density functional theory and non-equilibrium Green's function formulation with decoherence. We found that conductance is very sensitive to small changes in virus sequence. Among the 6 mutations in the Delta S region, D950N shows the largest change in relative conductance, reaching a surprising 4104.75%. These results provide new insights into the Delta variant from the perspective of its electrical properties. This may be a new method to distinguish virus variation and possess great research prospects. Graphical Abstract: ga1 Highlights: Theoretically analyzed the changes of electrical properties behind virus mutation. Constructing RNA:DNA hybrids structure to extract the electrical properties of RNA. Conductance is very sensitive to small changes in virus sequence. It is possible to detect SARS-CoV-2 variants mutations by electrochemical methods.